Signaling the credibility of private actors as public agents: transparency, independence, and expertise in environmental evaluations of products and companies. (August 2015) - Bullock, Graham
Abstract : Private firms are increasingly being regarded as moral agents of their stakeholders and the broader public. Stakeholders can use different types of evaluation organizations to monitor this division of moral labor, but must also monitor the credibility of this second layer of moral agents. This paper uses agency, signaling, and legitimacy theory to develop a novel conceptual framework showing how both firms and evaluation organizations send signals of their credibility as moral agents to earn grants of legitimacy from their moral stakeholders. The paper also describes how three specific characteristics of ratings and certifications – transparency, expertise, and independence – may signal different forms of credibility, appeal to particular stakeholder groups, and elicit different forms of legitimacy. A content analysis of the websites of 245 eco-labels, sustainability ratings and other forms of environmental evaluations reveals the multi-dimensional nature of these three characteristics, and finds that transparency is the most commonly-sent signal of credibility, followed by independence and then expertise. These results highlight the complexity of existing signals of credibility, and suggest several strategies – including voluntary credibility standards and a virtual information marketplace – that both private and public actors can pursue to improve the quality and accessibility of these signals of credibility.